Penerapan Inovasi Teknologi Oven Telur Asin dan Pengembangan Diversifikasi Produk Telur Asin di Kelurahan Mangunsari Semarang - Achmadi, Taofan Ali; Khoiron, Ahmad Mustamil; Ardiansari, Anindya (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
Mangunsari Village, Gunungpati District, Semarang City, possesses significant potential in duck egg farming, yet the development of local salted egg businesses faces several constraints. Key challenges include a time-consuming conventional production process (10-15 days) with high risk of egg spoilage, limited product diversification and unattractive packaging, and insufficient knowledge and skills among the community regarding technology, simple financial management, and digital marketing. These conditions lead to low productivity, limited product value, and restricted market reach. This community service program was designed to provide comprehensive solutions through technology innovation and empowerment. The implementation methods included socialization, workshops, practical demonstrations, and intensive assistance focusing on operating the Salted Egg Oven Machine, developing product diversification (flavor variants and packaging), business cash flow bookkeeping, and digital marketing using social media and e-commerce platforms. The achieved results demonstrate the potential to drastically cut down salted egg production time to approximately five hours, successful development of at least two new flavor variants, and improved packaging designs. The partners also showed increased capacity in operating and maintaining the oven, conducting basic financial recording, and utilizing digital technology for promotion and sales. This program tangibly enhances production efficiency, added value, and potential market expansion, expected to positively impact the community's productivity and economic welfare. The service contributes to achieving the SDGs in supporting food security, inclusive economic growth, and sustainable production.